IMPORTANCE OF MATERIAL DESIGN IN LANGUAGE TEACHING - Chulliev , Nuriddin Abdirashid ugli (Educational Research in Universal Sciences, 2023)
The standards and methods by which teachers deliver lesson materials have a significant impact on students’ success in the classroom. The quality of the teaching materials determines how effective a lesson is. To ensure that students are learning to their fullest potential, teachers must develop effective instructional materials. In addition to discussing different forms of teaching and learning materials, this article discusses material design in language instruction. There are given some instructions for language teachers on the development of materials for any aspect of language learning.